Interventional cardiology at left main coronary disease - Karaca, I.; Ilkay, E.; Arslan, N. (My University, 2000)
Medical follow up of severe stenosis of the left main coronary artery has poor prognosis. The survival ratio can be increased significantly by surgery. Angioplasty to left main coronary can be opplied technically but it is contraindicated due to acute occlusion, intimal dissection thrombus formation in which all of them causes sudden death. The stent and debulking applications are accepted as on alternative to surgery by a lot of authers. In this article we evaluated the results and reliability of angioplasty, stent, and intravasculer volume decreating debulking procedures in severe left main coronary stenosis.
Sol ana koroner lezyonlarinda girisimsel kardiyoloji
Keywords: Debalking; Left main stenosis; PTCA; Stent